Effect of Hatha Yoga and Jogging Against Anxiety in PSIK Faculty VIII Semester Students of Udayana University. - Made Wahyu Purwaningsih (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Anxiety is a respond from otonom nerve system against fear and anxiety that creates involuntary activity to the human body that’s including self defense. The stimulus can be derived from outside (interpersonal) or inside (interpsikis). If the stressor cannot been overcome by individual ability to adapt, this can create a conflict and becomes anxiety. Hatha yoga and jogging are one of the non pharmacology therapy that can decrease anxiety, because hatha yoga and Jogging can stimulate body to release endorphin hormones. This research aims to discover the influence of hatha yoga and jogging training to overcome anxiety in PSIK VIII semester student’s in Udayana University. This research is a quasi-experimental study. 38 total samples chosen by purposive sampling and divided into 2 groups, yoga group and jogging group. The yoga group given hatha yoga training twice a week in 90 minutes period and the jogging group given jogging training twice a week in 30 minutes period. Each group doing the training for 3 weeks Anxiety pre-test and post-test for both groups measured by Hamilton Anxiety Rating Scale questionnaire. The result shows 9.89 average decreasing score for yoga group and 6,21 average decreasing score for Jogging group. Based on independent sample t-test, this differences have a meaning in statistically, with t score in differences 1,717 and Sig. (2-tailed) score 0,095, that’s mean hatha yoga and jogging training didn’t have a significant effect for decreasing the anxiety of PSIK VIII semester student’s in Udayana University.